2015
DOI: 10.1128/jcm.01380-15
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Identification of Nontuberculous Mycobacteria from Clinical Isolates

Abstract: dMatrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the identification of nontuberculous mycobacterial (NTM) isolates was evaluated in this study. Overall, 125 NTM isolates were analyzed by MALDI-TOF and GenoType CM/AS. Identification by 16S rRNA/hsp65 sequencing was considered the gold standard. Agreements between MALDI-TOF and GenoType CM/AS with the reference method were, respectively, 94.4% and 84.0%. In 17 cases (13.6%), results provided by GenoType and MALDI-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Identification of mycobacteria has not reached an optimal level of routine testing yet and published studies showed discrepant performances, depending on spectrometer, extraction method, algorithm, library, media, and biomass used for the assays (15)(16)(17)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In this study, we compared two distinct databases of Vitek-MS, the Saramis v4.12 open database and the new IVD v3.0 closed database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of mycobacteria has not reached an optimal level of routine testing yet and published studies showed discrepant performances, depending on spectrometer, extraction method, algorithm, library, media, and biomass used for the assays (15)(16)(17)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In this study, we compared two distinct databases of Vitek-MS, the Saramis v4.12 open database and the new IVD v3.0 closed database.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially evaluated with mycobacterial intact cells (9)(10)(11)(12), but several investigators worked on improving inactivation and protein extraction (13)(14)(15)(16)(17)(18)(19)(20). Most published studies assessed the performance of MALDI-TOF BioTyper (Bruker Daltonics, Bremen, Germany) (15,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Few of them evaluated Vitek MS (bioMérieux, Marcy l'Etoile, France) (16,17,20,24,25,32).…”
mentioning
confidence: 99%
“…Differences were mainly due to the increased number of M. avium, M. gordonae, M. kansasii, and M. xenopi isolates correctly identified at a high-confidence level. Previous studies have already shown that the identification of M. avium and M. gordonae with a log(score) value of Ն1.8 was sometimes difficult to reach using older databases (3)(4)(5). However, the In conclusion, the use of the improved Mycobacteria Library v3.0 has increased the number of NTM isolates that attain a highconfidence identification level.…”
mentioning
confidence: 94%
“…The Mycobacteria Library database (Bruker Daltonik GmbH, Bremen, Germany) available so far (v2.0) provided low scores, particularly for NTM belonging to the slow-growing groups (3)(4)(5). In the present study, we assessed the power of a new database to identify NTM (i.e., Mycobacteria Library v3.0) using 109 isolates from 26 NTM species (Table 1) and compared the identification scores of version v2.0 and version v3.0.…”
mentioning
confidence: 99%
“…Previous studies of the identification of mycobacteria by MALDI-TOF MS used laboratory strain collections, i.e., pure cultures from frozen stocks, or worked only from solid media (4,7,8). In that setting, MALDI-TOF MS performs much better, but that is not informative for clinical laboratories, where identification of primary cultures is required to guide diagnosis and treatment.…”
mentioning
confidence: 99%